Allium sphaeronixum (Amaryllidaceae), A New Species from Turkey - Kocyigit, Mine; Salmeri, Cristina; Ozhatay, Neriman; Kaya, Erdal; Brullo, Salvatore (Mdpi, 2023)
In this paper, Allium sphaeronixum, a new species of the sect. Codonoprasum from Turkey, is described and illustrated. The new species is endemic to Central Anatolia, limited to the area of Nev(sic)sehir, where it grows on sandy or rocky soil at an elevation of 1000-1300 m a.s.l. Its morphology, phenology, karyology, leaf anatomy, seed testa micromorphology, chorology, and conservation status are examined in detail. The taxonomic relationships with the closest allied species, A. staticiforme and A. myrianthum, are also highlighted and discussed.
Keywords: Anatolia; endemic; sect. Codonoprasum; karyology; leaf anatomy; taxonomy; seed micromorphology